Identification of novel bacterial DNA gyrase inhibitors: An in silico study - Hamzeh Rahimi; Ali Najafi; Habib Eslami; Babak Negahdari; Mehrdad Moosazadeh Moghaddam (Wolters Kluwer Medknow Publications, 2016)
Owing to essential role in bacterial survival, DNA gyrase has been exploited as a validated drug target. However, rapidly emerging resistance to gyrase-targeted drugs such as widely utilized fluoroquinolones reveals the necessity to develop novel compounds with new mechanism of actions against this enzyme. Here, an attempt has been made to identify new drug-like molecules for Shigella flexneri DNA gyrase inhibition through in silico approaches. The structural similarity search was carried out using the natural product simocyclinone D8, a unique gyrase inhibitor, to virtually screen ZINC database. A total of 11830 retrieved hits were further screened for selection of high-affinity compounds by implementing molecular docking followed by investigation of druggability according to Lipinski's rule, biological activity and physiochemical properties. Among the hits initially identified, three molecules were then confirmed to have reasonable gyrase-binding affinity and to follow Lipinski's rule. Based on these in silico findings, three compounds with different chemical structures from previously identified gyrase inhibitors were proposed as potential candidates for the treatment of fluoroquinolone-resistant strains and deserve further investigations.